KUALITAS PELAYANAN PUBLIK PADA KANTOR EKSPEDISI J&T EKSPRESS DI SAMARINDA - Dian Eri Pratama, Maskan, dan Ibnu Ashari (Prodi Ilmu Administrasi Negara, 2021)
The purpose of this study was to determine the quality of service atthe J&T Express expedition office in serving users of J&T Express freightforwarding services.This type of research is descriptive qualitative. With the focus of thisresearch, namely: the availability of good employees, the availability of goodfacilities and infrastructure, being responsible to every customer, being ableto serve quickly and accurately, being able to communicate, guaranteeingthe confidentiality of every transaction, having good knowledge and abilities,trying to understand the needs customers, Able to give trust to customers.Data collection techniques include: Observation, Interview, Documentation,Literature study, and data analysis used, namely the interactive dataanalysis model (Miles & Huberman)Based on the research results, it can be seen that the service qualityat the J&T Express expedition office is good enough in providing services tocustomers. Starting from the place of service, service time, to dataconfidentiality are in accordance with existing procedures. Service users arevery satisfied with the services provided by the J&T Express expeditionoffice.So it can be concluded that the service quality at the J&T expeditionoffice is quite good and satisfying.